THE NATURE OF HUMAN BEINGS AND THEORETICAL FACULTIES (THEORY OF SPIRITUAL POWERS) IN ISLAM: AL-NAFS, AL-AQL, AL-QALB, AL-RUH, AND AL-SIRR VS. BLOOM'S TAXONOMY AND SOLO'S TAXONOMY - Selvi Syahfitri; Akhmad Sodiq (Jurnal Konseling Pendidikan Islam, 2026)
Studies on the nature of the human being in Islamic thought position the structure of the soul al-nafs, al-‘aql, al-qalb, al-ruh, and al-sirr as the foundational framework for understanding human potential, development, and spiritual orientation. Meanwhile, in the field of modern education, the Bloom-Anderson taxonomy and the SOLO taxonomy are used to map learners’ cognitive, affective, and psychomotor abilities. The differing paradigms between the Islamic concepts of the soul's faculties and contemporary educational taxonomies open an important epistemological space for dialogue in developing a more holistic learning theory. This article aims to explore the points of convergence and divergence between these two approaches. Specifically, the study seeks to: (1) describe the main structure of the faculties theory in Islam, including the functions of al-nafs, al-‘aql, al-qalb, al-ruh, and al-sirr; (2) compare these concepts with the cognitive hierarchy of Bloom-Anderson and the levels of understanding in SOLO; and (3) identify the potential for integrating the two to develop a value-based and spiritually grounded learning model. The methodology employs library research with comparative analysis of classical Islamic literature and modern educational taxonomies. Data were analyzed using categorization techniques and conceptual theme exploration. The findings show that the faculties theory offers a more comprehensive anthropological-spiritual foundation for understanding human development, extending beyond cognitive aspects toward tazkiyah (purification), moral awareness, and transcendental orientation. While Bloom-Anderson and SOLO emphasize cognitive achievements and structural understanding, the Islamic framework offers ethical and spiritual dimensions that can enrich instructional design. The integration of these paradigms enables the development of an educational model that not only strengthens higher-order thinking skills but also cultivates character, spiritual awareness, and inner harmony.